Peran Usia, Paritas, dan Pendidikan dalam Memprediksi Resiko Abortus pada Ibu Hamil di RSUD M Zein Painan - Hayu, Ramah; Fernando, Fenny; Pebrina, Melia; Fransisca, Dewi; Sari, Putri Permata (Universitas Pahlawan Tuanku Tambusai, 2025)
Abortion is one of the largest contributors to maternal morbidity and mortality in Indonesia. Maternal age, parity, and education are known to be important determinants in the incidence of abortion, especially in rural areas with limited access to health services. This study aims to determine the relationship between age, parity, and education of pregnant women with the incidence of abortion at M Zein Painan Hospital. This study was quantitative analytic with a cross-sectional design. The sample amounted to 151 pregnant women aged 0-20 weeks of pregnancy who were treated at M Zein Painan Hospital during 2024. Data were analyzed using the Chi-Square test. The results showed that the incidence of abortion had a significant relationship with maternal age (p=0.030), parity (p=0.022), education (p=0.003).These results indicate the importance of monitoring risk factors early in antenatal care to prevent abortion.